ASPEK PERLINDUNGAN HUKUM PRODUK KARYA ILMIAH TERHADAP KEGIATAN PENGUSAHA FOTOKOPY DI SAMARINDA - Pradya Putri Paramita (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT With the legal protections of the papers / books, it also shileded the special right held by the creator of a work especially papers / books. Keep it such protections prevents piracy, counterfeiting and the multiplacation of papers / books, and creator, the copyright holder, book publishing and the state no longer suffer losses. Great for the action of such copyright infringement. To prevent the infringement of copyright, especially article 15 UUHC No.19 2002 which is legal form the basis of the estabilishment of bussiness photocopy paper Scientifically, it is necessary to take preventive steps as follows; the estabilishment a copy of the business must obtain permission from depratemen judiciary; department of gave the judiciary in delivering the business license copy fito scientific work should provide requirements that would not saved of copyright; goverment must set the price of a copy fairly expensive price to photocopy more expensive of literature books, so people prefer to buy books literature; limiting the amount to be photographed copy; further narrow the use of the principle of fair dealing to implement these things, hope can reduce copyright violations more specialiazed books by way of fotocopy of which is contrary to article 15 UUHC No.19 2002, so awards of copyright can improve on more specialized in this field of work stationery / books and do not cause any harm in all area of liffe, particularly field of science